Political and diplomatic activity of the Courts of Navarre and the States of Béarn: the early years of the reign of Catherine I and the beginning of the “legal war” with the King of France (Edad Media. Revista de Historia, 2024)
The Navarrese and Béarn representative assemblies played an active political and diplomatic role between the last third of the 15th century and the beginning of the 16th century. Their important task of advising the kings of Navarre on important international issues was accompanied by political and diplomatic activity with ambassadors from other kingdoms, especially in times of instability and political confrontation, even issuing charters of belief and instructions to ambassadors from Navarre and Béarn, as it happened in 1507, a time of serious political conflict between the Navarrese and French monarchies.
Keywords: Representative Assamblies; "Cortes"; Monarchy; Diplomacy; Navarre; Béarn; France; Castile; Late Middle Ages